Study metastatic properties of triple negative breast cancer cells. - Zhou, Yinning. (2013)
Breast cancer is a disease which commonly and frequently occurs and threats women’s health seriously. Cancer cells have the ability to inhibit the ROS to achieve the aim to proliferate, survive and metastasize. From the results of our recent research, different kinds of cancer cells have different metastasis properties, and having the inherited genetic antioxidant modification is a possible explanation for triple-negative breast cancer cells to be high metastasis and malignant, especially for cancer stem cells. However, the mechanism of triple-negative breast cancer cells antioxidant ability has not been revealed. So we check the antioxidant ability to H2O2 and side population detection, in order to reveal the existence of cancer stem cells in 231-M1 and 231-M2, and study the antioxidant mechanisms of 231-M1 and 231-M2 compared with 231-C3 and MDA-MB-231. The results of this report demonstrates that the 231-M1 have much stronger metastasis ability compared with 231-C3 in vivo of zebrafish and the cancer stem cells may exist more in 231-M1 and 231-M2 compared with 231-C3 and MDA-MB-231 with significant discrepancy in side population distribution and antioxidant ability to H2O2.